2019
DOI: 10.1039/c9cy01709g
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-doped graphene edges: an efficient metal-free catalyst for the reduction of CO2 into methanol and ethanol

Abstract: Si doped graphene as a metal-free catalyst to convert CO2 to methanol and ethanol with high selectivity and activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 43 publications
1
51
0
Order By: Relevance
“…For DG electrocatalyst, Han et al 151 stated that their catalyst was stable for more than 10 h. Stability test at –0.6 V RHE showed that after 10 h, the current density dropped slowly from 2.1 to 1.5 mA cm −2 , whereas FE still retained over 70% during the entire process. They also compared their DG catalyst with previously reported graphene‐based catalysts and found that their catalyst was more stable under room temperature than previously reported ones 129,130,152–156 . Wu et al 131 found that their NGF catalyst was stable for at least 5 h, although the current density needs to be improved.…”
Section: Carbon‐based Metal‐free Electrocatalystsmentioning
confidence: 96%
See 1 more Smart Citation
“…For DG electrocatalyst, Han et al 151 stated that their catalyst was stable for more than 10 h. Stability test at –0.6 V RHE showed that after 10 h, the current density dropped slowly from 2.1 to 1.5 mA cm −2 , whereas FE still retained over 70% during the entire process. They also compared their DG catalyst with previously reported graphene‐based catalysts and found that their catalyst was more stable under room temperature than previously reported ones 129,130,152–156 . Wu et al 131 found that their NGF catalyst was stable for at least 5 h, although the current density needs to be improved.…”
Section: Carbon‐based Metal‐free Electrocatalystsmentioning
confidence: 96%
“…Mao et al 153 reported a new and emerging catalyst, named as metal‐free single atom, Si‐doped graphene edges (Si@G) for eCO 2 R with the aim of high catalytic activity. The authors stated that CO 2 activation efficiently occurred on Si@G due to a strong binding capability of –0.83 eV at the armchair edge and –0.65 eV at the zigzag edge, respectively.…”
Section: Carbon‐based Metal‐free Electrocatalystsmentioning
confidence: 99%
“…8 Under the mild conditions, metal-free catalysts also exhibit a high activity and selectivity to some chemical reactions, such as water splitting, fuel cells, and N 2 fixation processes. [9][10][11][12][13][14][15] As a typical two-dimensional (2D) metal-free material, pure graphene and BN have been wildly investigated due to their fascinating physical and chemical properties. 16 However, since the free flowing of π electrons of sp 2 carbon materials and large band gap of BN, they are inert for many chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to TM atoms, metal‐free catalysts have the advantages of being cheap, and environmentally friendy . Under the mild conditions, metal‐free catalysts also exhibit a high activity and selectivity to some chemical reactions, such as water splitting, fuel cells, and N 2 fixation processes …”
Section: Introductionmentioning
confidence: 99%
“…32 Some literature has reported silicon doped graphene (SiG) as a promising metal-free catalyst for N 2 O, SO 2 , CO reduction and green energy as well. [33][34][35][36][37][38] Chen et al stated that silicon-doped graphene can be an ideal NO, NO 2 detection sensor, and N 2 O reduction metal-free catalyst. Their research showed that while adsorption of these molecules on pristine graphene is very weak, silicon doping increases the interaction of these molecules (nitrogen and oxygen) in different ways with graphene.…”
Section: Introductionmentioning
confidence: 99%